Spinal Subdural Hematoma Following Meningioma Removal Operation - Jun, Hyo Sub (The Korean Spinal Neurosurgery Society, 2014)
Although blood contamination of cerebrospinal fluid (CSF) after an intracranial operation can occur, the development of a symptomatic spinal hematoma after craniotomy has been anecdotally reported and it is uncommon reported after a supratentorial meningioma removal operation. We report a case of spinal subdural hematoma following a supratentorial meningioma removal operation and discuss the mechanism of spinal subdural hematoma (SSDH) development. A 54-year-old woman presented with lumbago and radicular pain on both legs 4 days after a right parietooccipital craniotomy for meningioma removal. Only the straight leg raising sign was positive on neurologic examination but the magnetic resonance imaging (MRI) demonstrated a lumbosacral spinal subdural hematoma. The patient received serial lumbar tapping, after which her symptoms showed improvement.